The CELSR1 polymorphisms rs6007897 and rs4044210 are associated with ischaemic stroke in Chinese Han population. (January 2015) - Zhan, Yi-Hong; Lin, Yi; Tong, Sui-Jun; Ma, Qi-Lin; Lu, Cong-Xia; Fang, Ling; Wei, Wei; Cai, Bin; Wang, Ning
Abstract Background: Recently, CELSR1 was identified by genome-wide association studies (GWAS) as a susceptibility gene for ischaemic stroke (IS) in Japanese individuals. Aim: The goal was to examine whether CELSR1 variants are associated with IS in the Chinese Han population. Subjects and methods: This study genotyped two single nucleotide polymorphisms (SNPs) of CELSR1, rs6007897 and rs4044210, in a Chinese sample of 569 IS cases and 581 controls and assessed their genotype and allele associations with IS. Results: The results showed that rs6007897 and rs4044210 variants of CELSR1 were significantly (p < 0.01) associated with IS. These associations remained after adjustment for age, gender, smoking status, hypertension, diabetes mellitus and hypercholesterolemia. In addition, a significant association was observed of rs6007897 and rs4044210 of CELSR1 with large artery atherosclerosis (LAA), a sub-type of IS (p < 0.01). Conclusion: Taken together, the present study has proven for the first time that CELSR1 is a susceptibility gene for IS in the Chinese Han population, especially for LAA.